Komparasi Efisiensi Teknis Bank Umum Konvensional (BUK) dan Bank Umum Syariah (BUS) di Indonesia Dengan Metode Data Envelopment Analysis (DEA) - Abdul Wahab; Muhammad Nadratuzzaman Hosen; Syafaat Muhari (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Comparation of Technical Efficiency Between Conventional Banks and Islamic Banks in Indonesia Using DEA MethodThis research is to compare the levels of technical efficiency between BUK and BUS by employing non-parametric Data Envelopment Analysis (DEA). This research assigns Third Party Funds, Labor Expenses and Fixed Assets which are input variable, meanwhile Total Credit and Other Incomes are determined as Output Variables. This research also examines the Profitability of BUK and BUS by Using Panel Regression Model with CAR, LDR, NPL and BOPO as independent variables, where ROA and ROE are dependent variables. The result showed that the average technical efficiency of the Conventional Banks is better than that of the Islamic Banks. That is because of the inefficient utilization of Input Variables, namely Third Party Funds, Labor Expenses and Fixed Assets in the Islamic Banks  DOI:10.15408/aiq.v6i2.1229